Variabilidade genética de Dinoponera quadríceps Santschi (Hymenopera: Formicidae): filogeografia de uma espécie endêmica do semiárido nordestino - Galheigo, Cíntia Brito de Souza (2011)
Dinoponera quadriceps Santschi 1921 (Formicidae: Ponerinae) is endemic in northeastern Brazil. Are relatively large ants, whose workers grow up to 3 cm long and show no morphological differences between castes. In this species the reproduction is performed by workers known as fertilizer "gamergate”. This research sets out to study the genetic variability through mitochondrial DNA to elucidate the distribution patterns of the species. The results of PCR + RFLP showed low variability and showed no consistency to the standards micro and macrogeographical. Thus, 473pb were sequenced gene Cytochrome Oxidase I (COI) from 34 individuals, revealing only 31 haplotypes and 93 variable sites. The nucleotide diversity found among all individuals analyzed was considered low, however, the haplotype diversity share was high. The phylogenetic inference by Bayesian and Maximum Parsimony separated the individuals of D. quadriceps in two major clades according to geographic distribution. The hypothesis that work on the level of moderate to high genetic differentiation of populations of D. quadriceps in the Caatinga ecoregion has been accepted, showing that populations have a high genetic variability and a strong structure both within and between ecoregions analyzed.